Pharmaco-economics: Minute-based cost of sevoflurane in pediatric short procedures and its relation to demographic variables - Preet Mohinder Singh; Anjan Trikha; Renu Sinha; Rashmi Ramachandran; Vimi Rewari; Anuradha Borle (Wolters Kluwer Medknow Publications, 2013)
Background: Inhalation agents account for significant cost of short daycare procedures. The estimation of this cost to pre-calculate expected expenditure is not available in literature. As for intravenous agents, their relations to weight and other demographic parameters are also not well established. The present study aims to evaluate the above concern. Materials and Methods: A total of 100 pediatric (ASA I, II) patients scheduled for ophthalmological examination under anesthesia (EUA) were included in the study. Following premedication, anesthesia in all children was induced using incremental concentrations of sevoflurane at a flow of 6 l with 1:1 oxygen:nitrous oxide ratio. Upon induction, the flows were reduced to 2 l, keeping sevoflurane at 1 to 2 minimum alveolar concentration (MAC). Using Dion's equation, the costs for induction and maintenance with sevoflurane were calculated for each patient. Results: The cost per minute of sevoflurane was found to be Rs. 13.23. Unlike intravenous agents, no significant correlation was found to exist between sevoflurane consumption with age or weight. The sevoflurane consumption was also not influenced by the gender. The total cost of EUA correlated most strongly with duration of maintenance phase, followed by induction duration.